Operations and effects of the generalized system of preferences. United Nations. New York. 1974. (Document No. TD/B/C-5/15). (The Pakistan Development Review, 1975)
The developed economies, except the USA and Canada, have each imple¬mented a Generalized System of Preferences (GSP) in order to encourage exports of the developing countries. Since the tariffs imposed on the imports from the developing countries are relatively small under the GSP, the developing countries have an advantage in the exports of commodities covered by the GSP., The GSPs. of different countries vary in product coverage, depth of tariff cuts', safeguard measures for the protection of domestic industry, and the rules of origin. For a •comparative analysis of the GSPs of different countries, an evaluation of the im¬pact of the overall GSP on the exports of the developing economies, and of sugges¬tions-for devising ways and means for expanding the exports of the developing countries, several committees were formed by the UNCTAD Secretariat. The Report under review is a collection of documents prepared by those committees, including document- Nos. TD/B/C-5.2 to TD/B/C-5.9. These documents are arranged under three heads, viz. General Report, Consideration of some inportant aspects of the GSP, and the Case Studies. The main issues discussed in these re¬ports are: Special measures in favour of the least developed countries; Effect of the GSP on the tariff advantages enjoyed by the African countries associated with the European Economic Community (EEC); Analysis of the rule of origin; and Effects of the GSP of the EEC countries, Japan and the UK on the export earnings of the beneficiary countries.